A review on eco-city evaluation methods and highlights for integration. (January 2016) - Dong, Huijuan; Fujita, Tsuyoshi; Geng, Yong; Dong, Liang; Ohnishi, Satoshi; Sun, Lu; Dou, Yi; Fujii, Minoru
Highlights: Evaluation methods were reviewed to facilitate pathway for eco-city transition. Six methods covering environment, economy and decision making were focused. Their system boundaries, advantages and disadvantages were further compared. Methods integration for different eco-city transition purpose was discussed. Abstract: Current rapid urban development, particularly in Asian cities, is facing various challenges, such as resource depletion, environmental emissions and increasing pressures on responding climate change. It is critical for decision-makers to raise the appropriate urban development strategies so that cities can move toward sustainable development. In this regard, well-designed evaluation methods are valuable for managing environmental development and providing guidelines to improve sustainable urban development. Six well-known assessment methods for environment and sustainability assessment, namely, input–output analysis (IOA), life-cycle analysis (LCA), ecological footprint (EF), carbon footprint (CF), emergy analysis and cost benefit analysis are selected. Each method has its own advantages and disadvantages. This paper provides a comprehensive literature review on these methods and proposes an integration of different methods so that the holistic performance of one eco-city initiative can be scientifically evaluated and key problems can be identified. Such an integration can solve the problems that each single method is facing so that valuable policy insights can be identified for urban decision-makers to prepare more appropriate urban strategies.